Some Non-price Explanatory Variables in Fertiliser Demand: The Case of Irrigated Pakistan (The Pakistan Development Review, 2000)
It follows from the experience of World economies that rising and balanced use of fertilisers is the key factor in agricultural productivity [FAO (1995); SFS and STI (1996); Habib-ur-Rehman (1982) and Pinstrup-Anderson (1976)]. In the case of Pakistan the stepped up fertiliser use has been argued to be incritable to realise existing untapped yield potential of major crops [Johnston and Kilby (1975)] and to induce yield increasing technological change in future [John Mellor Associates and Asianics Agro-Dev. International (1993)]. Although proper malnutrition involves the use of primary, secondary and micro-nutrients, Nitrogen (N), Phosphorus and Potassium (K) or NPK is generally considered to be sufficient to harvest normal crop yields [FAO and IFA (1999)]. Given this situation, this paper looks at various factors that determine fertiliser use in Pakistan. Although price of fertiliser is a critical factor in this respect [Schultz (1965) and Johnston and Cownie (1969)], only non-price factors are considered in this paper due to limitations of data. Apart from this introductory section, the paper comprises of three more sections. The following Section 2 explains the data and the empirical model. Section 3 presents the results. Section 4 summarises the main findings along with their policy implications.